Модель математичного програмування з цілочисельними змінними визначення оптимального складу та завантаження енергоблоків теплових електростанцій та гідроагрегатів гідроакумулюючих електростанцій при покритті добового графіка електричних навантажень енерго - Shulzhenko S.V.; Turutikov O.I.; Ivanenko N.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2020)
To solve actual task of founding new dispatch modes for Hydro Pumping Storages Stations’ (HPSS) units and thermal power plants (TPPs) units with the possibility of observing the set level of the frequency recovery reserve (secondary reserve) in the predefined volumes placed at the thermal power plants the new Mixed-Integer Programming mathematical model was proposed.The model takes into account the specific technical and economic indicators of the main types of Ukrainian TPP units, in particular, the change in generation capacity in the range from minimum to nominal load levels, as well as the rate of change of load. The mathematical model takes into account specific operations mode of Ukrainian HPSS’s units – practical impossibility to change power consumption and generation during operation of unit in pumping and generating modes.Calculations using proposed mathematical model are resulting in finding optimal dispatch schedule of Ukrainian HPPS’s units for Integrated Power System (IPS) daily load profile balancing with an hourly resolution of the forecast schedule of electrical loads.The proposed model is realized with MathProg language of GLPK linear programming package. It takes only about 30 seconds to perform one calculation, which allows its practical use for the formation of several modes of dispatching of generating equipment of the IPS of Ukraine when covering the load profile with their subsequent analysis and finding the mode that best provides the requirements of balance reliability. In particular, this speed of calculation makes it possible to use the model for a series of profiles of electricity generation of Wind Farms and Solar Generation, which have stochastic properties of power generation. This creates the preconditions for the development of a mathematical model using stochastic programming methods to obtain robust solutions.The proposed mathematical model can also be used as a basis for improving mathematical models for dispatching other types of generating capacity, in particular hydroelectric power plants and energy storage.